Authentic learning as a case of becoming - Parnell, Renee; Smith, Dianne (Curtin Uni, 2012)
Navigating authentic learning involves risk. Staff who adopt such strategies to engage students and foster deep learning are confronted by the ambiguity and fluidity inherent in learning environments that enable students to be independent, responsible learners and which invite other stakeholders into the mix in real time. Such settings involve trust and an ability to embrace circumstances as they unfold rather than as initially structured. The outcome is a state of becoming. Becoming can be understood in terms of the project, the strategy, the students’ transformation, and the outcome, and involves unit objectives, content, activities and outcomes. In this paper, a one week community-based intensive project, held in and with a culturally diverse rural Western Australian community, is described through the experiences of the interior architecture staff, both full time and sessional, and juxtaposed with student reflections and feedback. In an interpretative framework, the expert-insider stories and reflections identify the characteristics of academics in situations that are beyond control and outside traditional ways of knowing. The experiences are captured through personal reflections and collective discussions as the project unfolds. Personal and professional aspects of the staff members merge, being held in common and in contrast, and inform the process that emerges.This case study illustrates the opportunities that exist for students (and staff ) to transform through such projects (Tweddle, 2000; Demirbilek et al. 2007).This paper seeks to assist other academics to navigate the complexity of community-based projects and to encourage interior architecture academics to embrace the risks inevitable in such situations. It was predicted that individual staff would experience a range of emotions over such projects, and that strategies would need to be flexible and responsive to the students’ activities; and that responses would require diverse modes of interaction as the students transformed and/or become intimidated by the reality of such opportunities. This reflective paper reveals that the key considerations in attempting such projects are to develop strategies for students to deal with their preconceived risks and how they are realised, whilst navigating their learning experience and personal state of becoming.